Preparation and Study of the Optical Properties of Recycled Materials of Polymethyl methacryalate Doped with Different Ratios of 4-(2- Pyridylazo) Resorcinol Monosodium Salt Hydrate - Zainab J. Sweah; Fatima H. Malk; Muhsen Chelab Muhsen; Baheya abdulbaqi (مجلة بغداد للعلوم)
This paper presents an incoming method of developing a novel optical sensor using polymethylmethacrylate was reused with the presence of the ethanol-derived resin from Frankincense (1:1) (wt:wt%-(2-Pyridylazo) Resorcinol Monosodium Salt Hydrate) (azo dye) by solution casting technique. The prepared samples were Scanning Electron Microscopes(SEM),and studied by UV-VIS spectrophotometer for wavelengths   400-800nm, the absorbance increased; however, when it exceeded 7%, the absorbance value decreased, and the behavior was identical to that of the transmittance. The absorption coefficient and Extinction coefficient and optical energy gap at 5% is the best value. were also computed. Based on the results obtained the study was reached about the possibility of using the prepared films to develop optical fiber sensors from recycled polymethylmethacrylate, with good specifications that are considered a good treatment of trash in the environment.